2008
DOI: 10.1007/s10493-008-9156-8
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of Neoseiulus paspalivorus and Proctolaelaps bickleyi, candidate biocontrol agents of the coconut mite Aceria guerreronis: spatial niche use and intraguild predation

Abstract: The eriophyid mite Aceria guerreronis occurs in most coconut growing regions of the world and causes enormous damage to coconut fruits. The concealed environment of the fruit perianth under which the mite resides renders its control extremely difficult. Recent studies suggest that biological control could mitigate the problems caused by this pest. Neoseiulus paspalivorus and Proctolaelaps bickleyi are two of the most frequently found predatory mites associated with A. guerreronis on coconut fruits. Regarding b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…For example, Griffiths et al (2004) observed that socially familiar fish consumed more food items per time unit than unfamiliar fish and suggested that familiarity allowed to switch attention from within-group aggression to foraging. However, higher feeding rates do not necessarily indicate enhanced foraging efficiency and do not necessarily translate into enhanced life history traits (Stearns 2000; Illius et al 2002; Lawson-Balagbo et al 2008). In our study, familiar mites apparently optimized energy gain per prey item eaten or reduced energy invested in other activities, allowing to feed less at the same developmental speed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Griffiths et al (2004) observed that socially familiar fish consumed more food items per time unit than unfamiliar fish and suggested that familiarity allowed to switch attention from within-group aggression to foraging. However, higher feeding rates do not necessarily indicate enhanced foraging efficiency and do not necessarily translate into enhanced life history traits (Stearns 2000; Illius et al 2002; Lawson-Balagbo et al 2008). In our study, familiar mites apparently optimized energy gain per prey item eaten or reduced energy invested in other activities, allowing to feed less at the same developmental speed.…”
Section: Discussionmentioning
confidence: 99%
“…This species thrived on the coconut eriophyid, Aceria guerreronis Keifer as primary food source resulting in shorter developmental time, higher ovipositon rate and higher intrinsic rate of increase than on any other diet (Lawson-Balagbo et al, 2007). Neoseiulus paspalivorus is dorso-ventrally flattened giving it an advantage in accessing the area under the bracts (Lawson-Balagbo et al, 2008b). This species is thus cited as a promising candidate for the biological control of the coconut eriophyid (LawsonBalagbo et al, 2008a).…”
Section: Neoseiulus Longispinosus (Evans)mentioning
confidence: 99%
“…Fungivory has also been reported for other species in this same genus, namely Proctolaelaps pygmaeus (Muller) (Shereef et al 1980), P. striatus Westerboer (Afifi et al 1984), P. bickleyi (Lawson-Balagbo et al 2008b) and P. deleoni Nawar, Childer and Abou-Setta (Nawar 1992). The determined rates of population growth of P. bulbosus were slightly lower than that determined for P. bickleyi by Lawson-Balagbo et al (2007a), on both A. guerreronis and R. aff.…”
Section: Parametersmentioning
confidence: 75%